The Different Faces of Abortion : A juxtaposition of herbal and physical abortifacients. - Samantha Liu (Ars Medica, 2022)
Abortion is a medical procedure that can be employed to save lives or as an expression of bodily autonomy, but it is more often in the minds of the people as an issue rife with ethical controversy. Abortion sits at the intersections of race, gender, sexuality, (dis)ability, religion, and more in medicine: women and people who can become pregnant were and are afforded fewer legislative rights. The doctor/trainee/patient experience is also impacted by the controversies surrounding abortion: providers unable to legally provide abortions may have tried to help in other ways, and patients without the guidance of providers may seek dangerous options if they feel they have no other choice. The danger involved with using physical methods of self-induced abortion like knitting needles, clothes hangers, or throwing oneself down a flight of stairs are far more visually obvious than, for example, a flower. However, the use of herbal abortifacients also involves significant risk of severe morbidity and mortality. By juxtaposing these methods, the viewer is stimulated to think of the history of abortion and the legal, social, and medical context of abortion.